(untitled) (Washington, D.C., 1999)
In diverse regions around the country, impending crises over dwindling natural resources and conflicts over land use have given birth to a new approach to environmental management and policymaking. Known as bioregional assessment, the approach gives science and scientists a crucial role in the policymaking process, bringing together experts on a range of issues to assess existing ecological and social conditions and to provide a base of knowledge from which to develop policy options and management decisions.
Keywords: Environmental management,Environmental policy; Case studies,Case studies; United states,United states